Performance investigation of ground source heat exchanger with desiccant-based hybrid cooling system in humid climate. Issue 5 (September 2019) - Heidarinejad, Ghassem; Berardi, Umberto; Rayegan, Saeed
Abstract: A desiccant-based hybrid cooling is among the most cost-effective air conditioning systems. The main purpose of this paper is the assessment of the potential of ground-assisted direct evaporative cooler together with a desiccant evaporative cooling cycle integrated with a ground source renewable energy for the pre-cooler process. Simulation results obtained using the TRNSYS software are compared with experimental data. The simulation of the mentioned systems are conducted in Bari (south of Italy), Palermo (south of Italy) and Ramsar (north of Iran) for the humid-mild climate of July. Assuming the low regeneration temperature (Treg ) for the desiccant wheel is one of the highlights of this paper. Utilizing ground source heat exchanger (GSHE) will result in increase of the system potential in providing thermal comfort. The average thermal comfort achieves in Bari, Palermo and Ramsar in 95.72%, 93.94% and 93.15% of the time from 6 AM to 6 PM in July with utilizing the combination of GSHE and desiccant cooling system. The COP of this cycle is highly dependent on the Treg, and varies in the range of 0.35-0.53, 0.34-0.6 and 0.34-0.52 for the maximum Treg of 50 °C in Bari, Palermo and Ramsar, respectively.